CITIZENSHIP THEORY AND ITS IMPLEMENTATION IN BUILDING CIVIC VIRTUE IN INDONESIA - Saskia Nur Anggraeni; Naufa Ulfiyah; Arief Rahman Hakim; Eulis Afidah; Aila Azkiya Fitriani (Adisam Publisher, 2025)
This study aims to analyze citizenship theory and its implementation in building civic virtue in Indonesia. The research is motivated by the crucial role of citizenship education in forming ethical, participatory, and character-driven citizens in accordance with Pancasila values. The challenges of globalization and modernization have led to shifts in moral values and increased individualism, which potentially weaken the spirit of civic virtue. Therefore, this study focuses on how citizenship theories, such as liberal, republican, and communitarian, can be adapted to strengthen civic practices in the Indonesian context. The research employs a descriptive qualitative method with a literature study approach, examining various scholarly sources, journals, and relevant policy documents. Data were analyzed using content analysis techniques to identify patterns of citizenship values and the application of civic virtue in various spheres of life. The findings indicate that citizenship theories provide a conceptual foundation for shaping responsible and actively participating citizens in societal and state life. Civic virtue is understood as a set of values, including honesty, social responsibility, care, and mutual cooperation (gotong royong), that support the healthy functioning of socio-political life. In Indonesia, the implementation of these values is reflected in Pancasila and Citizenship Education, national character-building programs, and community social movements. However, its application still faces obstacles, such as inconsistent curriculum implementation, the influence of digital media, and a decline in collective awareness. In conclusion, strengthening civic virtue needs to be pursued through value-based education rooted in Pancasila, inclusive public policies, and social exemplarity from various elements of society. This study is expected to provide a conceptual contribution to the development of citizenship science and the cultivation of civilized citizen character.